Cardiovascular Profile of Xanthelasma Palpebrarum. (20th June 2013) - Dey, Anupam; Aggarwal, Ramesh; Dwivedi, Shridhar
Abstract : Xanthelasma palpebrarum (XP) are yellow plaques that occur most commonly near the inner canthus of the eyelid and are often associated with atherosclerosis, dyslipidemia, and coronary artery disease. This study was planned to address the issue of associated cardiovascular morbidity in xanthelasma patients attending our cardiac clinic. Materials and Methods . A total of 61 patients were detected to be having xanthelasma and constituted the study group. The control group constituted of 130 apparently normal individuals. Each patient underwent detailed history, examination, and investigations. Results and Discussion . The most prevalent age group was 40 to 60 years. Males outnumbered females. A percentage of 39.3% of cases had concomitant nicotine addiction. Dyslipidemia was present in 60% of cases, hypertension in 37.7%, prehypertension in 8.77%, diabetes mellitus in 18.03%, and prediabetes in 26.3%. Smokers and obese patients with xanthelasma had a higher prevalence of hypertension. Coronary artery disease (CAD) was found in 6.56% of XP cases. The waist circumference and diastolic blood pressures were significantly higher in XP patients. Conclusion . A significant number of cases of xanthelasma palpebrarum are combined with smoking, central obesity, hypertension, diabetes mellitus, and dyslipidemia which are the major risk factors for CAD. Efforts should be made to rule out the same in high-risk xanthelasma subjects.